DIGITAL TRANSFORMATION OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN REALIZING INDONESIA’S ECONOMIC INDEPENDENCE IN THE ERA OF INDUSTRY 4.0 - Gita Sari Dewi; Zainal Abidin Sahabuddin; Susilo Adi Purwanto````ro (Bajang Institute, 2023)
Digital transformation in the industrial era 4.0 has changed the new face of Micro, Small and Medium Enterprises (MSMEs) to achieve sustainable and inclusive economic independence. The potential for natural wealth, human resources and opportunities as an agricultural country are factors that influence success in the global economy. In its implementation, MSMEs have had mental readiness for the application of digital literacy. However, this will not run synergistically without simultaneous and gradual efforts to guard and improve digitalization technology in agricultural businesses. The fishery sub-sectoral agricultural business for catfish species is a supporting sector for Indonesia's food security. With this urgency, the application of digitization of agricultural businesses must be guarded from the production chain to distribution on a national and international scale.